An Unusual Localization of a Cardiac Pseudoaneurysm Complicated by Paravalvular Leak in a Patient with Prosthetic Heart Valves - Vatankulu, Mehmet A.; Sonmez, Osman; Akkaya, Mehmet; AYDIN, CEMALETTİN; AYDIN, CEMALETTİN (My University, 2016)
Mini-Abstract An 58-year-old male was admitted to the hospital with exertional dyspnea. He had a history of mitral and aortic valve replacement with St. Jude prosthetic valve twenty years ago. Transesophageal echocardiography showed paravalvular mitral leak and a false chamber, which was expanding during systole and communicating to the right atrium. Real time three-dimensional transesophageal echocardiography demonstrated the origin and flap of the false lumen that was opening during ventricular systole and closing at ventricular diastole from the left ventricular inside. The patient underwent redo aortic and mitral valve surgery.